Tracking the Evolving Spatial-Temporal Gene Networks. Issue 28 (2015) - Gong, Weikang; Wan, Lin
Abstract: The modeling and identification of the spatial-temporal gene networks in transcriptome scale is a challenging problem. To investigate the molecular mechanism of genes in a dynamic and systematic fashion, we develop a novel method for tracking the spatial-temporal modules of gene network reconstructed from the brain development gene expression data. A statistical model based method for module/graph mathch is proposed to track the evolving gene networks. We apply this method to brain spatial-temporal networks and provides new insights into the molecular mechanisms of brain development as well as the functions of the the schizophrenia associated genes.